The Impact of The Free Halal Certification Program (Sehati) on The Revenue Growth of Micro, Small, And Medium Enterprises (MSMES) - Hidayanti Wildan, Firda; Abdun Natsir, Mohamad; Zulpawati, Zulpawati (UIN Mataram, 2024)
The Indonesian government's role in optimizing the halal economy includes initiatives such as the Free Halal Certification Program (SEHATI) for Micro, Small, and Medium Enterprises (MSMEs), which has demonstrated a substantial impact on income levels. Halal certification has been shown to positively affect revenue growth among MSMEs. In Mataram City, in particular, MSMEs experienced significant increases in income following the acquisition of halal certification. The SEHATI program for MSMEs in Mataram is coordinated by various institutions, including the Halal Center at UIN Mataram, the Ministry of Religious Affairs, the Department of Cooperatives and MSMEs, and the Department of Industry and Trade. The aim of this study is to implement and analyze the impact of the SEHATI Free Halal Certification Program on the income growth of MSMEs in Mataram City. This research employs a qualitative methodology, utilizing field research techniques such as observation, interviews, and data collection through documentation. The findings indicate that the SEHATI program has had a significant impact on the income levels of MSMEs in Mataram City. The implementation of the SEHATI program involves several key elements: first, effective communication; second, human resource development; third, the role and attitude of program implementers; and fourth, the organizational structure, emphasizing the importance of collaboration among implementing bodies. The provision of free halal certification through the SEHATI program has notably increased the income of MSMEs in Mataram City, empowering business owners to market their products with enhanced confidence.